Bahasa Arab dalam Islam: Kunci pemahaman Al-Quran dan spiritualitas Islam - Nisa', Ismi Khoirun (Maliki Interdisciplinary Journal, 2024)
Arabic has a very important position in Islam because it is used as the main language in the Quran, the holy text of Muslims. The Quran was revealed in Arabic and is seen as a source of law, moral guidance, and spiritual guidance for Muslims around the world. In this abstract, we explore the uniqueness of Arabic in the Quran, including phonetic beauty, grammatical complexity, and depth of meaning. Understanding Arabic as the language of the Quran is key to deepening religious experience, increasing understanding of Islamic teachings, and perceiving the spiritual values contained in sacred texts. By making Arabic the focus of learning, individuals can gain a deeper insight into Islam and strengthen the spiritual connection with the Quran.